40 Improving Urinary Catheter Documentation and Care in Geriatric Wards. (16th March 2021) - Costa, A V; Zhunus, A; Storey, B; Sait, M S; Shah, S; Sanei, F; Mathew, J; Heitor, M
Abstract: Introduction: NICE guidelines state that urinary catheter insertion, changes and care should be documented. Duration of catheterization is directly linked to the risk of developing a catheter-associated UTI. Furthermore, Public Health England has announced a national aim to reduce the incidence of Gram-negative bacteraemia by 50% by March 2021, and targeting catheters is one of the first steps. Local problem: These issues are relevant to the elderly population at Princess Royal University Hospital, where documentation surrounding catheters was found to be inadequate. Despite there being an Electronic Patient Record (EPR) order for catheter insertion and monitoring available, this was not being used. Our primary aim was for all patients to have this order. We also hoped to reduce the weekly rate of catheter days (catheter days per 100 bed days), and improve documentation in clinical notes. Methods: We focused on two medical wards and sampled all patients admitted over a period of 4 months who had a catheter at the time of data collection. We identified catheterized patients and whether they had an EPR catheter order on a daily basis. Additional parameters such as indication, insertion date, inserter, and documentation standards were extracted from EPR on a weekly basis. Patients were kept "live" and contributing to catheter day calculations until they were no longer on the ward or if the catheter was removed. Interventions: We implemented changes over 2 PDSA cycles. Interventions included the addition of catheter columns to boards and education sessions for doctors and nurses (cycle 1), as well as catheter posters, alert cards, and circulation of emails with guidance to doctors and nursing staff (cycle 2). Results: A total of 87 patients were analysed during the project. There was an increase in EPR orders being used, with the 100% target being reached on the final data collection point, and with data showing a significant shift above baseline. Furthermore, there was a decrease in the weekly rate of catheter days, but changes were difficult to sustain. We also saw a general improvement in documentation standards. Conclusion: By improving documentation and reducing unnecessary catheterization, we hope to have reduced the overall risk of infection whilst improving patient comfort and experience. Lessons may be transferrable to other trusts.